Effectivess of defensemen's play in the offensive zone : the impact of defensemen's positional changes on goals and scoring changes in offensive zone offensive play - Yli-Junnila, J. (Haaga-Helia University of Applied Science, 2019)
The role of offensive zone offensive play has increased in modern ice hockey with the increase in size of the offensive zone. Teams now need to have various forms of offensive zone team systems in order to increase the puck possession and scoring chances. The fast pace of the ice hockey today requires having all five players involved in team`s play system in every zone. In offensive zone offensive play the ability to utilize the offensive effectiveness of the defensemen can be a valuable asset for teams` success.